2012
DOI: 10.1039/c2jm34280d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of CdTe nanocrystals for high performanced Schottky thin film solar cells

Abstract: We report the synthesis of CdTe semiconductor nanocrystals (NCs) with multi-armed, rod and tetrapod shapes, developed by a facile solution process using a cadmium carboxylate as the precursor at moderate temperatures of 220-300 C. It was found that the size and morphology of the CdTe NCs were related to synthesis parameters such as the reaction temperature, carboxyl chain length and carboxylic acid. Based on these CdTe NCs, photovoltaic cells (PVC) in simple Schottky diode configuration of ITO/CdTe/Al were fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…More recently, Luther et al [42] investigated the effects of different size, shape, and crystal structure of the initial NCs on the CdTe NC solar cells. They found that inks of predominantly wurtzite tetrapod-shaped NCs with arms about 5.6 nm in diameter formed better films than inks composed of smaller tetrapods, irregular faceted NCs, or spherical zinc blende NCs, which was consistent with the previous reports [12]. A smooth and low-defect CdTe NC film can be formed in the case of using spherical CdTe NCs because spherical NCs could assemble with higher packing density and, therefore, more easily convert into continuous films with less void space and larger grains.…”
Section: Cdte/zno Heterojunction Solar Cellssupporting
confidence: 82%
See 2 more Smart Citations
“…More recently, Luther et al [42] investigated the effects of different size, shape, and crystal structure of the initial NCs on the CdTe NC solar cells. They found that inks of predominantly wurtzite tetrapod-shaped NCs with arms about 5.6 nm in diameter formed better films than inks composed of smaller tetrapods, irregular faceted NCs, or spherical zinc blende NCs, which was consistent with the previous reports [12]. A smooth and low-defect CdTe NC film can be formed in the case of using spherical CdTe NCs because spherical NCs could assemble with higher packing density and, therefore, more easily convert into continuous films with less void space and larger grains.…”
Section: Cdte/zno Heterojunction Solar Cellssupporting
confidence: 82%
“…Comparing to alky-phosphine acid-capped CdTe NCs, fatty acid (such as oleic acid)-capped CdTe NCs [35] have many advantages, such as low cost, low fabrication temperature, and fatty acid is easily removed during the ligands' exchange process, which improves purity of the final NCs products. Sun et al [12] synthesized CdTe NCs by this method and fabricated solar cells with the Schottky structure of ITO/CdTe/Al. The best device showed a PCE of 5.15% under AM 1.5 G illumination.…”
Section: Schottky Junction Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,27 The final CdTe NCs products were dissolved in a hybrid solvent of pyridine and 1-PrOH (with a volume ratio of 1 : 1), with a concentration of 50 mg mL À1 . Then the mixture was heated to 240 1C at a rate of 8 1C/10 minutes under a N 2 flow.…”
Section: Fabrication Of Cdte Cdse Ncs and Zno Precursormentioning
confidence: 99%
“…In the above reports, the low device performances originate from two obvious drawbacks. 23 CdTe NC solar cells with the inverted structure have many benefits over the devices with the normal structure reported above. 21 On the other hand, the series resistance of the devices was large, leading to the fill factor (FF) being below 50%.…”
Section: Introductionmentioning
confidence: 98%